Lost and win-back customers: towards a theoretical framework of customer relationship reactivation - Lopes, Luisa (2013)
The aim of this study is to explore dynamics of customer relationships in the posdissolution phase. The specific challenges with which companies with high levels of churn and competitive pressure are faced are addressed. Focusing relationships between the service provider and its individual customers, a theoretical framework of Customer Relationship Reactivation (CRR) is proposed based on ending literature and equity theory. A mixed methodology is used with an exploratory firms survey, a case study and in depth interviews. We believe it is possible to apply the theoretical framework in companies delivering a mix of goods and services. We describe and illustrate the value of the framework which includes key determinants such as customer characteristics, relationship characteristics, cognitive factors, emotional factors, reasons for switching and reactivation barriers.